Effects of Joint Therapy Mobility Exercises on The Level of Osteoarthritis Knee Joint Pain in The Elderly Padang - Rachmawaty M Noer; Ika Sheilla (IJECA (International Journal of Education and Curriculum Application), 2018)
Osteoarthritis (OA) is a degenerative joint disease, where the overall structure of the joint undergoes pathological changes. One of the changes that occur in the musculoskeletal system can cause mobility disorders. The impact that will occur in the elderly with osteoarthritis is likely to experience a decrease in musculoskeletal function. This study aims to determine the effect of osteoarthritis knee joint pain levels before and after exercise therapy for joint mobility. The design of this study uses a quasi-experimental method with a Pre and Post Test without Control research design. The sample in this study consisted of 30 respondents. The sampling method in this study is accidental sampling. Research data were analyzed using the Wilcoxon test. It is known that more than half of respondents who have osteoarthritis are in the age range of 45-59 years, which is 46.7% (14 respondents). The results showed that in general osteoarthritis pain before ROM was in the range of 80% moderate pain, and the results showed that in general osteoarthritis pain after ROM was in the range of 76.7%. Data analysis found that the p-value was 0,000 (p = <0.05) indicating that there was an effect of exercise joint mobility on the level of osteoarthritis knee joint pain in the elderly in the Posyandu of the Belakang Padang elderly. This research is expected to be able to contribute and develop nursing, as a material for making policies on psychological approaches in the form of exercise therapy for joint mobility in overcoming joint pain in patients with osteoarthritis. osteoarthritis by involving variables that affect the level of pain.